Geographic Fragmentation in the EU Market for e-Books: The case of Amazon - Michail Batikas; Estrella Gomez-Herrera; Bertin Martens (European Commission, Joint Research Centre (JRC), 2015)
This study examines geographical market segmentation in the market for e-books in the EU, based on data from the Amazon Kindle e-books store, the market leader. Residents in all EU countries have access to the Amazon US Kindle store. However, access to Amazon's 6 e-book stores in the EU (UK, Germany, France, Spain, Italy and the Netherlands) is restricted to residents in each of these countries and in 4 neighbouring countries with which they share a language. There is no cross-border store access between these 6 countries. Because e-book catalogues are 93% overlapping between these 6 stores, cross-border access restrictions do not significantly affect cross-border availability in the EU6+4=EU10. Even for the remaining EU18 cross-border availability is very high because they have access to nearly all e-books in the EU6 stores via the Amazon US store. They have no direct access to the EU6 e-book stores however. Lifting digital access walls for Amazon e-book stores in the EU would result in a small increase only in the book titles available to EU consumers. E-book prices vary between Amazon EU stores, and between EU and US e-book stores. Currently, EU10 consumers can find price arbitrage opportunities between their local store and the US store only. Consumers in the remaining EU18 can buy from the US store only. Lifting geographical access restrictions would increase price arbitrage options, especially for EU18 e-book consumers. However, the welfare impact is difficult to predict as it might lead to increased price convergence, with winners and losers. E-book prices excluding VAT appear to be negatively correlated with VAT rates. This reduces consumer price variation despite variations in VAT rates across countries. The discrepancy between universal access to the US e-book store and geographically restricted access to the same e-books in EU stores indicates that access is driven by commercial considerations rather than objective legal barriers related to the EU copyright management regime. Market segmentation piggy-backs on but is not driven by the copyright regime.
Keywords: F15; 330; Amazon; e-books; geographical market segmentation; EU market; electronic publishing